2020
DOI: 10.21037/atm-20-5669
|View full text |Cite
|
Sign up to set email alerts
|

Fangchinoline attenuates cardiac dysfunction in rats with endotoxemia via the inhibition of ERK1/2 and NF-κB p65 phosphorylation

Abstract: Background: Cardiac dysfunction is a complication commonly encountered by patients with endotoxemia.Fangchinoline (Fan) is a natural bisbenzylisoquinoline alkaloid. This study aimed to investigate the cardioprotective effect of Fan against lipopolysaccharide (LPS)-induced acute cardiac dysfunction.Methods: Rats were administered with Baicalin (100 mg/kg) and Fan (30 or 60 mg/kg) via intraperitoneal injection (i.p.) for 3 days, followed by LPS treatment (10 mg/kg, i.p.). The rats were randomly grouped (n=10): t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…4 h). Moreover, NF-κB p65 subunit phosphorylation reflects the activation of NF-κB [ 33 ]. Here, we observed that glycogen mobilization inhibited NF-κB activation at 24 h following OGD/R and that this inhibitory impact was blocked once GP was deficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 h). Moreover, NF-κB p65 subunit phosphorylation reflects the activation of NF-κB [ 33 ]. Here, we observed that glycogen mobilization inhibited NF-κB activation at 24 h following OGD/R and that this inhibitory impact was blocked once GP was deficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous lines of evidence have revealed that Fan induces autophagy via the activation of AMPK/mTOR/ULK1 signaling pathway ( Xiang et al, 2021 ). Meanwhile, Fan has also been reported to inhibit the PI3K/Akt and MAPK signaling pathways in several diseases ( Li et al, 2017 ; Jiang F. et al, 2020 ; Chen et al, 2020 ; Villa et al, 2020 ; Chen et al, 2022 ). However, the exploration of Fan’s impact on proteasome regulation remains relatively limited and restricted to human cancer cells and articular chondrocytes ( Chuu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cepharanthine have been reported to protect renal injuries induced by ischemia/reperfusion [ 36 , 37 ], chemotherapeutic reagent cisplatin [ 38 ], streptozotocin-induced diabetic nephropathy [ 39 ], transient middle cerebral artery occlusion (tMCAO) or subarachnoid hemorrhage induced brain injury [ 24 , 40 ] or dextran sulfate sodium (DSS)-induced ulcerative colitis [ 41 ]. Protective functions of fangchinoline have been reported in models of oxidative glutamate toxicity [ 42 ], streptozotocin-induced diabetic nephropathy [ 43 ] as well as or LPS-induced cardiac dysfunction [ 44 ]. In addition to its well-studied anti-hypertension and anti-arrhythmia function [ 45 ], berbamine is reported to protect ischemia/reperfusion-induced heart injury [ 46 , 47 ] and ethanol-induced liver damage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%